2007
DOI: 10.1002/dev.20225
|View full text |Cite
|
Sign up to set email alerts
|

Are 6‐month‐old foals sensitive to dam's influence?

Abstract: A recent study has shown that gently handling dams in front of their few days old foals may strongly influence the development of human-foal relationships. In the present study, we test whether 6-month-old foals remain sensitive to their dams' influence. The study was performed on 16 foal-mare dyads, with half of the mares receiving positive contacts from the experimenter in presence of their 6-month-old foals (n = 8) whereas the other mares were not handled (n = 8). All foals were tested 15 and 30-35 days lat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0
3

Year Published

2009
2009
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 57 publications
1
7
0
3
Order By: Relevance
“…This finding agrees with the results of a number of other recent studies, which suggest that individual personal traits may significantly modify behavior and physiological response in wide range of species including horses (Hausberger et al, 2004;Henry et al, 2007;Ijichi et al, 2013;LeScolan et al, 1997).…”
Section: Cortisol Concentrationssupporting
confidence: 94%
“…This finding agrees with the results of a number of other recent studies, which suggest that individual personal traits may significantly modify behavior and physiological response in wide range of species including horses (Hausberger et al, 2004;Henry et al, 2007;Ijichi et al, 2013;LeScolan et al, 1997).…”
Section: Cortisol Concentrationssupporting
confidence: 94%
“…In horses, the exclusive relationship between foal-mare dyads induces foals to learn from their mothers since birth [23], but the strength of their mothers' influence decreases as the foals grow older [24]. However, one- and two-year-old horses are susceptible to the influence of unrelated adults [14].…”
Section: Discussionmentioning
confidence: 99%
“…Pioneer studies showed that young domestic horses are sensitive to adult influences (e.g. mothers [23], [24], unrelated adults [14]). Here, we show for the first time that adult-young ratios are directly correlated to the expression of aggression and to the social cohesion of young horses in their family group, aspects that affect the social skills of young horses.…”
Section: Introductionmentioning
confidence: 99%
“…Thus one of the strongest bonds in the animal kingdom is, at least partly, a feeding bond. Interestingly, the detachment in the feeding bond goes together with a detachment in the affectionate bond [7]. More generally, food sharing has been described as a reciprocal act of physical affiliation [8] and an essential component for the development of pair bond [9].…”
Section: Introductionmentioning
confidence: 99%